1973
DOI: 10.1063/1.1654780
|View full text |Cite
|
Sign up to set email alerts
|

Laser damage threshold for dielectric coatings as determined by inclusions

Abstract: By studying the morphology of threshold damage and observing for the first time the predicted ``pulse duration-inclusion size'' relationship, it is shown that the threshold for laser damage to nonabsorbing dielectric coatings is determined by the presence of metallic or highly absorbing nonmetallic inclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1975
1975
2011
2011

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Laser damage of dielectric thin films in the nano-second regime is mainly initiated by nanometric absorbing defects [8][9][10] inherent to the manufacturing process. A useful method to obtain information on the damaging defects is to study the laser damage statistics: defect statistical model.…”
Section: Discussionmentioning
confidence: 99%
“…Laser damage of dielectric thin films in the nano-second regime is mainly initiated by nanometric absorbing defects [8][9][10] inherent to the manufacturing process. A useful method to obtain information on the damaging defects is to study the laser damage statistics: defect statistical model.…”
Section: Discussionmentioning
confidence: 99%
“…. On the other hand, this very same effect has proven to be harmful and costly in high-power applications where local scatterers and absorbers can enhance the local electric field and induce strong local temperature rise leading [9,10] to the damage of expensive large optical components. But in any case, there has recently been a growing interest in photo-induced thermal effects in various domains where metallic nano-structures are at stake.…”
Section: Introductionmentioning
confidence: 99%
“…Pit formation as a result of inclusions has also been extensively studied both experimentally 11,[37][38][39] and theoretically. 40,41 These studies have shown that nodular defect ejection depends on seed diameter and on incident laser fluence.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of damage morphology studies has been widely recognized and many researchers have attempted to understand the relationship between damage morphology, damage threshold, and a variety of parameters such as wavelength, [4][5][6] fluence, 7 film material (composition and properties), 4,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] optical design 9,27 and film thickness, 28 pulse length, 4,5,7,[29][30][31] and laser pulse repetition rate. 29,32 Understanding these relationships may allow process optimization so as to let the coating evolve (e.g.…”
Section: Introductionmentioning
confidence: 99%